Sex offenders and the internet - Sheldon, Kerry (Wiley, 2007)
Sex offending on the internet -- The issue of child pornography -- What we know about paedophilia -- Creating and controlling the internet sex offender -- What internet sex offenders do -- The childhood histories of paedophiles -- Sexual abuse and sexualisation in the childhoods of paedophiles -- Coping with life through abuse and child pornography -- Relationships in childhood and adulthood : security and attachment -- Sexual fantasy and paedophile offenders -- Distorted thinking -- Desisting from child abuse -- Epilogue: What has been learnt and what shall we do?